Interactive Media for Make-Up Black and White Photo Color (IMFM) as Medium Study : Activity and Efectiviness Outcomes - Tyas Asih Surya Mentari; Ambiyar Ambiyar; Rahmi Oktarina; Prima Minerva; Linda Rosalina (Universitas Negeri Padang, 2023)
Education will produce scholarly, intellectual and technological human resources to increase competitiveness. Black and white photo and color makeup is one of the core competencies of a beautician. There are still limitations in learning black and white photo and color makeup in the Department of Makeup and Beauty, Faculty of Tourism and Hospitality, Padang State University. Students are still struggling to master the basics of black and white and color photo makeup and have not been able to apply materials and cosmetics correctly. This study aims to develop interactive multimedia learning media for black and white photo and color makeup. This research is a development using the 4-D method (define, design, develop and disseminate). Quality and practicality were observed in teachers, students and practicing professionals. The results show the following; (1) The validity of interactive multimedia as a valid medium (2) The practicality of interactive multimedia as a practical medium based on the responses of teachers and students after the test (3) Effective efficacy in increasing the learning activities of the students with a very good category and the learning results of the students before and after using interactive multimedia as a medium. Based on the findings of this study, it is concluded that interactive multimedia as a medium is valid, practical and effective to be used as a learning medium in black and white photo and color makeup lessons.